Questions spatiales et recherche numérique au Centre allemand d’histoire de l’art (DFK Paris) - Anne Klammt (Humanités Numériques)
Since 2014, the German Center for Art History Paris has had a department for Digital Humanities, which conducts its own research and supports projects at the DFK Paris by designing and implementing digital research. The projects have produced extensive data sets and have modeled space and spatial phenomena in different ways. Their results offer numerous opportunities for further research.